USING THE ZOD TOOL TO VALIDATE DATA INPUT INTO A FUNCTION - Sousa, Murilo; Dian, Mauricio (Revista Interface Tecnológica, 2024)
This article explores the use of the Zod library for schema validation in Typescript, demonstrating how this technique can improve data entry into functions, guaranteeing not only the security but also the correctness of the data. Using Zod's parse method, the study not only checks that the data conforms to the predefined schemas, but also converts the data into the appropriate format. This process is fundamental to maintaining data integrity and avoiding common errors associated with the manipulation of input data. The methodology adopted involved a detailed analysis of practical use cases where Zod has been implemented, providing a clear understanding of how schema validation can contribute to safer and more efficient development practices. The article justifies the choice of topic by the growing need for more robust and reliable applications, where data errors can have serious consequences. The aim of this study is to highlight the importance of data validation in improving the quality and reliability of applications, highlighting how Zod can be a valuable tool for developers looking to implement these rigorous practices.
Keywords: Typescript; Zod; Validation; Data Manipulation